2007
DOI: 10.1016/j.wear.2006.05.022
|View full text |Cite
|
Sign up to set email alerts
|

3D characterisation of tool wear whilst diamond turning silicon

Abstract: Nanometrically-smooth infrared silicon optics can be manufactured by the diamond turning process. Due to its relatively low density, silicon is an ideal optical material for weight sensitive infrared (IR) applications. However, rapid diamond tool edge degradation and the effect on the achieved surface have prevented significant exploitation. With the aim of developing a process model to optimise the diamond turning of silicon optics, a series of experimental trials were devised using two ultra-precision diamon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 17 publications
3
24
0
2
Order By: Relevance
“…The selection of cutting parameters and coolant was based on previous established research work of diamond turning of silicon to attain high optical quality machining [27]. Large nose radius tools were used as they provide strong edge geometry to withstand higher frictional resistance and higher cutting forces.…”
Section: Experimental Planmentioning
confidence: 99%
“…The selection of cutting parameters and coolant was based on previous established research work of diamond turning of silicon to attain high optical quality machining [27]. Large nose radius tools were used as they provide strong edge geometry to withstand higher frictional resistance and higher cutting forces.…”
Section: Experimental Planmentioning
confidence: 99%
“…Данной проблеме посвящено большое количество научных исследований, и во всех работах упоминается хрупкопластич-ный переход. Это явление, наблюдающееся при обработке кремния и других хрупких материа-лов, проявляется в том, что при определенных условиях их можно обрабатывать как пластич-ные [4][5][6][7][8][9].…”
Section: физикоunclassified
“…До этого момента резание выполня-лось в пластичном режиме. В работе [6], посвященной обработке крем-ния лезвийным алмазным инструментом, опи-саны стойкостные эксперименты с использова-нием различных смазочно-охлаждающих жид-костей (СОЖ) и при разных геометрических параметрах инструмента, а также при неодина-ковых кристаллографических ориентациях ал-маза, закрепленного в резце. В исследовании по определению влияния СОЖ на стойкость ин-струмента применялся алмазный резец с радиу-сом при вершине r = 0,5 мм и углами  = -25,  = 10.…”
Section: физикоunclassified
“…They concluded that ductile machining can be achieved by using a diamond tool with a negative effective rake angle. With regard to the cutting tool performance, Durazo-Cardenas et al [14] characterised the wear mechanisms of the diamond tool, and found that micromachining and chipping were the most frequent wear modes. Born and Goodman [15] also studied the effect of varying the machining conditions, such as depth of cut, feed rate, and cutting speed in combination with changing tool geometry on the diamond tool wear modes.…”
Section: Diamond Machining Of Optical Silicon Surfacesmentioning
confidence: 99%